2012
DOI: 10.1155/2012/396573
|View full text |Cite
|
Sign up to set email alerts
|

Demethoxycurcumin Retards Cell Growth and Induces Apoptosis in Human Brain Malignant Glioma GBM 8401 Cells

Abstract: Demethoxycurcumin (DMC; a curcumin-related demethoxy compound) has been recently shown to display antioxidant and antitumor activities. It has also produced a potent chemopreventive action against cancer. In the present study, the antiproliferation (using the MTT assay, DMC was found to have cytotoxic activities against GBM 8401 cell with IC50values at 22.71 μM) and induced apoptosis effects of DMC have been investigated in human brain malignant glioma GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
(54 reference statements)
0
37
0
Order By: Relevance
“…These findings suggest that C2 induces Bcl-2 mediated apoptosis more effectively than curcumin or C3. A study published by Huang et al [63] also examined the effects of C2. They showed that C2 had IC 50 of 22.7  μ M in GBM 8401 cells and that apoptosis was induced by decreasing the mitochondrial membrane potential and caspase-dependent pathways similar to other studies of curcumin [63].…”
Section: Mechanism and Preclinical Datamentioning
confidence: 99%
“…These findings suggest that C2 induces Bcl-2 mediated apoptosis more effectively than curcumin or C3. A study published by Huang et al [63] also examined the effects of C2. They showed that C2 had IC 50 of 22.7  μ M in GBM 8401 cells and that apoptosis was induced by decreasing the mitochondrial membrane potential and caspase-dependent pathways similar to other studies of curcumin [63].…”
Section: Mechanism and Preclinical Datamentioning
confidence: 99%
“…The pleiotropic effects of curcumin can be summarised in the following [6] apoptosis by induction of caspase activity (demethoxycurcumin) [10] Mcl-1 downregulation [12] Radiosensitisation [15] Chemosensitisation [16] Diabetes/metabolic syndrome Improve insulin sensitivity [17] increases the levels of anti inflammatory cytokines like adiponectin [19,20] improved endothelial function [21] decrease in inflammatory cytokines and oxidative stress markers [21] Skin diseases decreases IL-22 levels [23] Osteoarthritis (Curcuma domestica) apoptosis of synovial adherent cells. [30] Neuroprotection Alzheimer disease(in vitro)…”
Section: Curcumin On Depression:-mentioning
confidence: 99%
“…DMC was shown to reduce multiplication of these cells and decrease their survival and lead to apoptosis by induction of caspase activity [10] .In a similar study, the in vitro effect of curcumin was studied on multiple human glioblastoma cell lines, both primary and recurrent, where it was found to exhibit a dose dependent decline in proliferation of these cells, which could be explained by hampering the STAT-3 pathway of signalling [11] .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The cell lines were treated with the formulation of curcuminoid-Poloxamer 407 for 24 h, then harvested, and fixed in 1 mL cold 70% ethanol for at least 8 h at −20°C. DNA was stained in PI/RNaseA solution, and the cell cycle (at least 10,000 single cells) was detected by flow cytometry (FACSCalibur, BD, USA) [24]. Data was analyzed by WinMDI 2.8 free software (BD, USA).…”
Section: Evaluation Of Apoptosismentioning
confidence: 99%